Innovations in university management - Sanyal, Bikas C. (Unesco, International Institute for Educational Planning, 2020)
Many factors have contributed to the increased pressure on institutions of higher education worldwide to become more cost-effective. In 1990, the International Institute for Educational Planning (IIEP) launched an international research program on the problems of higher education management at the institutional level to create a knowledge base on the methods of better utilization of existing resources. The research began with an extensive literature review and creation of an information base, and continued with the writing of a series of papers on methodological issues and the preparation of 14 in-depth case studies on different types of innovations. The results of these activities were used to prepare a set of training materials for intensive training courses. The exchange of individual university experiences in managerial innovations in these training courses provided an additional knowledge base for IIEP. This book attempts to synthesize all these results from the research and training programs. The book's sections are: (1) "The Research Programme"; (2) "The External Environment of Higher Educational Institutions"; (3) "Improving University Management to Meet Changing Needs"; (4) "Improving Selected Areas of University Management" (including financial, academic staff, research and economic links, space, and educational delivery systems); and (5) "Prospects for Improving Management." Chapters contain references. (EV)